Pengaruh Implementasi Kebijakan terhadap Kinerja Pengelolaan Keuangan Nagari di Kabupaten Pasaman - Maulidya, Indrilita (JESS (Journal of Education on Social Science); Vol 3 No 2 (2019): Special EditionDO - 10.24036/jess/vol3-iss2/183, 2019)
This study aims to determine the effect of policy implementation on the performance of nagari apparatus in nagari financial management in Pasaman Regency. This research was motivated by the lack of implementation of policies on nagari financial management in Pasaman Regency. This study used a quantitative research method conducted on 12 nagari in Pasaman Regency with a population of 96 consisting of walinagari, nagari secretary, three heads of affairs and three section heads. While the number of samples as many as 8 8 respondents were determined using the Slovin formula. In this study data collection used a Likert Scale with data collection techniques using the Proportionate Stratified Random Sampling technique. The results of this study show that partially the communication sub-variables have an effect of 20.5%, sub-variables of resources by 2.6%, sub-disposition variables by 17.1% and sub-variables of birourism structure by 13.5% on the performance of nagari financial management . While simultaneously the policy implementation variables provide a significant influence on the performance of nagari financial management in Pasaman District with a simultaneous influence of 12.8%.